Second International Congress on Islamic Civilization in Southern Africa: Developments and Future Perspectives (American Journal of Islam and Society, 2016)
In 2006 the first International Congress of Islamic Civilization in SouthernAfrica was hosted by AwqafSA (www.awqafsa. org.za) and IRCICA (Centrefor Islamic History, Art, and Culture www.ircica.org) at the University of Johannesburg.IRCICA, the prime mover and funder of this and similar conferencesand congresses worldwide, has been actively promoting these platformsto bring academics, scholars, researchers, and other stakeholders together tohighlight research outputs and findings that reflect upon the status and positionof Muslim minorities worldwide. Since Southern African Muslim communitiesform an integral part of Africa’s Muslims, it decided to host a follow-upevent in the region.IRCICA once again teamed up with AwqafSA, which had been in closecontact with IRCICA since the 2003 Uganda “Islamic Civlization in EastAfrica” conference. For this congress, AwqafSA partnered with the InternationalPeace College of South Africa (IPSA) and the University of KwaZulu-Natal (UKZN). It also teamed up with ITV, Radio Al-Ansaar, and the MinaraChamber of Commerce. Since UKZN was the main academic partner, thecongress was held from March 4-6, 2016, at the Senate Chambers of UKZN’sWestville campus.The organizers’ objectives for the congress were to (a) increase people’sknowledge of the history and heritage of Southern Africa’s Muslims, (b)strengthen cooperation among Muslim and African nations and their peoplesby producing and disseminating Islamic and cultural knowledge, and (c) offera forum for the true understanding of Islamic culture in the world.Donal McCracken (acting dean of research, College of Humanities) officiallywelcomed the delegates. Following his opening remarks, the audienceheard from the representatives of the Congress Organizing Committee.Zeinoul Cajee (CEO, AwqafSA), Halit Eren (director-general, IRCICA), andShaykh Ighsaan Taliep (IPSA). Eren underscored the importance of these ...